Supervisors-in-Training: The Experience of Group-Format Supervision-of-Supervision (Canadian Journal of Counselling and Psychotherapy, 2014)
Using procedures inspired by Consensual Qualitative Research methodology (CQR), we examined the transcripts of 10 doctoral students who had been interviewed about their experiences participating in a supervision-of-supervision (SOS) group while currently providing supervision to master’s-level counsellors-in-training. Five categories were identified: (a) SOS as a valuable context for professional development, (b) the benefits of SOS, (c) the role of the supervisor in SOS, (d) hindering aspects of group-format SOS, and (e) frustrations with the structure of SOS within the curriculum. These categories are elaborated, and a discussion and implications that flow from them are presented.